Tracing the transformation of the "ruwatan" rituals in Java from the fifteenth to the twenty–first century - Wijayanto, Muhammad Heno; Suparta, I Made; Setyani, Turita Indah (Wacana, Journal of the Humanities of Indonesia, 2025)
This article explores the transformation of ruwatan (purification) rituals in Java from the fifteenth century to the twenty-first century, focusing on the changes that occurred based on archaeological relics and texts related to ruwatan rituals. A thorough study in connecting archaeological relics, such as reliefs in Sukuh Temple, with puja (ritual worship) texts used in ruwatan rituals and the transformation of these texts from their origins within Kawi culture through to the Islamic period and the present day, has not been attempted. This research aims to identify and analyse the transformation of ruwatan rituals from the fifteenth century, as reflected in the reliefs at Sukuh Temple and in texts such as Aji Saraswati and Bhīma Swarga, to texts of the modern era, including the Serat Centhini, Serat Hong Ilaheng, and Lakon Wayang Ruwatan Murwakala. Through an interdisciplinary approach combining archaeological and manuscript-based research, this study shows how ruwatan rituals remain relevant and adapt to the changing socio-cultural context of Java, maintaining cosmological balance and strengthening the order of Javanese society over time.